Quality of life and cardiorespiratory function in chronic heart failure: effects of 12 months' aerobic training. Issue 1 (July 1996) - Kavanagh, T.; Myers, M. G.; Baigrie, R. S.; Mertens, D. J.; Sawyer, P.; Shephard, R. J.
Abstract : OBJECTIVE: To examine the long-term benefits and safety of aerobic training in patients with chronic heart failure. DESIGN: Non-randomised control trial with 52 weeks follow up. SETTING: Outpatient cardiac rehabilitation referral centre. PATIENTS: Patients with compensated chronic heart failure (mean (SD) age 62 (6) years, New York Heart Association stage III, initial resting ejection fraction 22 (7)%). Experimental group of 17 men, 4 women; control group 8 men, 1 woman. INTERVENTIONS: Experimental group: progressive, supervised aerobic walking programme for 52 weeks. Control group: standard medical treatment. MAIN OUTCOME MEASURES: Six-minute walk distance, progressive cycle ergometer test to subjective exhaustion, disease-specific quality of life questionnaire, and standard gamble test, all measured at entry, 4, 8, 12, 16, 26, and 52 weeks. RESULTS: Control data showed no changes except a small trend to improved emotional function (P = 0.02 at 12 weeks only). Fifteen of the 21 patients completed all 52 weeks of aerobic training; two withdrew for non-cardiac reasons (16, 52 weeks). Three were withdrawn because of worsening cardiac failure unrelated to their exercise participation (4, 4, 8 weeks), and one had a non-fatal cardiac arrest while shopping (16 weeks). Gains of cardiorespiratory function plateaued at 16-26 weeks, with 10-15% improvement in six-minute walk, peak power output, and peak oxygen intake linked to gains in oxygen pulse and ventilatory threshold and reductions in resting heart rate. Marked improvements in quality of life followed a parallel course. CONCLUSIONS: Aerobic training is safe and beneficial in compensated chronic heart failure. Gains in aerobic function and quality of life persisted over a programme lasting 52 weeks.